2009
DOI: 10.1242/dmm.003509
|View full text |Cite
|
Sign up to set email alerts
|

The role of gamma interferon in innate immunity in the zebrafish embryo

Abstract: SUMMARY The zebrafish genome contains ten genes that encode class II cytokine-like peptides, of which the two that are related most closely to mammalian interferon gamma (IFN-γ) were named IFN-γ1 and IFN-γ2. Although the zebrafish has become a popular model system to study immune mechanisms, and although interferons are central regulators of immunity, which zebrafish cytokines correspond functionally to mammalian IFN-γ has not been established. We used zebrafish embryos to assay the functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 47 publications
1
68
0
Order By: Relevance
“…Recent in vivo studies on Ifn-g target gene induction showed that the response elicited by Ifn-g1 and Ifn-g2, as measured by target gene induction, was identical for both Ifn-g (14). Morpholino-mediated knockdown of either one of the ifn-g genes does not render the embryos susceptible to bacterial infection.…”
mentioning
confidence: 99%
“…Recent in vivo studies on Ifn-g target gene induction showed that the response elicited by Ifn-g1 and Ifn-g2, as measured by target gene induction, was identical for both Ifn-g (14). Morpholino-mediated knockdown of either one of the ifn-g genes does not render the embryos susceptible to bacterial infection.…”
mentioning
confidence: 99%
“…IFNs are best known for their vital roles in innate immune system. Recently, studies focused on the immune-related functions of IFN-γ had been carried out in many teleosts, such as goldfish 42 and zebrafish 10 . We have carried out the expression analysis of the Japanese flounder IFN-γ in tissues infected with LPS and revealed the expression regularity.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon (IFN) which plays an important role in innate immune system is a protein secreted from cells in response to invasion by pathogens and virus. In mammals, IFN is classified into type-I IFN (α, β, ε, δ, τ and ω), type-II IFN (γ) and type-III IFN (λ) based on their differences in primary structure, serology and their most likely time of evolutionary divergence 8,9,10 . Interferon-gamma (IFN-γ) is a pleiotropic proinflammatory and antiviral cytokine, which was initially identified in PHA-activated mammalian lymphocyte supernatants 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish, there are four members of type I IFNs (Aggad et al, 2009;Lopez-Munoz et al, 2009), and two members of type II IFNs, IFNc1 and IFNc2 (Igawa et al, 2006;Sieger et al, 2009). Previously we confirmed both types of zebrafish IFNs activate zebrafish IRF9 promoter in epithelioma papulosum cyprini cells (EPC) (Shi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, zebrafish Danio rerio genome has four IFNu genes (DrIFNu1/ 2/3/4, or named DrIFN1/2/3/4) most similar to mammalian type I IFN, and two IFNc genes (DrIFNc1/2) orthologous to mammalian type II IFN (Aggad et al, 2009;Lopez-Munoz et al, 2009;Sieger et al, 2009). To determine whether two types of fish IFNs could induce crucian carp viperin expression, the roles of these zebrafish IFNs in activation of crucian carp viperin promoter and induction of viperin mRNA and proteins were investigated.…”
Section: Induction Of Viperin By Two Types Of Fish Ifnsmentioning
confidence: 99%